English Language University Teachers’ Difficulties in Research Engagement: A Case Study in Vietnam: Kesulitan Guru Universitas Bahasa Inggris dalam Keterlibatan Penelitian: Studi Kasus di Vietnam - Le, Huong Hoang (JEES (Journal of English Educators Society), 2017)
The study uses a qualitative case study framed within a socio-cultural framework to investigate Vietnamese English language university teachers’ difficulties in their research engagement. The study was conducted among 21 English language university teachers in Hong Duc University in Vietnam. Skype semi-structured interview was employed to collect necessary data to explore teacher participants’ perceived obstacles to research. The findings of the study show that there was a gap between Vietnamese authorities’ expectations of research outputs and the realities of English language university teachers’ research capabilities. Such gap has caused serious challenges to those teachers and prevented them from effectively engaging in research. On the one hand, Vietnamese authorities hope to increase universities’ research output to keep up with the international academic ranking. On the other hand, the working realities of university teachers hinder their engagement in research. However, no official investigation has been done to reduce such gap and the enforcement of research activity in universities has been taken for granted. In this sense, the significance of this study is an opportunity for English language university teachers to voice their opinions about the enforced nature of research activity in universities in Vietnam.